About technology workshops in teaching russian language in high school (Eurasian Journal of Philology Science and Education, 2019)
The article discusses the technique of using technology workshops in teaching Russian in highschool. The characteristics of this technology are characterized: productive, creative, a combination ofindividual, steam and group work, lack of evaluation, criticism and pressure, a joint search for solutions.The author of the article proposes options for conducting technology teaching workshops on the materialof two topics: «The artistic style. Style and genre features» and «Publicistic style. Style and genre features». Describes all the stages of the workshop and the form of work. The article presents such methodsand techniques as building associative rows, working with statements and text, creating an associativepicture, «Recover the text», reflection «Plus or minus-interesting», etc., contributing to the assimilationof the material through the implementation of practical work. With specific examples, it is shown that,depending on the content of the topic and the objectives of the lesson, the algorithms of the workshopsmay vary